Economics of development (W.W. Norton & Co. LondonGB, 2001)
Introduces the concept and measurement of development, theories that have arisen to explain development, and the body of data that has been amassed to recognise and define development. Considers the role of markets versus planning and government control as the preferred means for guiding the economy and the question of how to make development sustainable.
Keywords: ECONOMIC POLICY